Materi Pendidikan Islam dalam Hadis Nabi dan Relevansinya dengan Konsep dan Sistem Pendidikan Modern - Baharun, Mays Brim; Mustofa, M. Zainul; Maghfiroh, Khoirotul Laili (Dirasat: Jurnal Manajemen dan Pendidikan Islam, 2018)
This article discusses Islamic educational material in the ?ad?th of the Prophet and its relevance to the concepts and systems of modern Islamic education. Referring to the importance of Islamic education in Indonesia, it is necessary to study the materials that must be used as a guide and basis for Islamic education. Islamic education material is the experiences of learning the Islamic religion which are arranged in such a way as to be presented or delivered to students. This study has two objectives, namely knowing and understanding the content of the ?ad?th that discuss educational material; as well as knowing the relevance of Islamic education material to the systems and concepts of modern Islamic education. This article concludes that Islamic education materials recorded in the Prophet’s ?ad?th have relevance to the systems and concepts of modern Islamic education.